Working-Conflict Effect on Knowledge Sharing with Organizational Communication in Makassar New Port - Kusno, Muh Zulfiqar; Munizu, Musran; Wahda, Wahda (Faculty of Economics and Business, Hasanuddin University, 2022)
This study aims to analyze the effect of work conflict on knowledge sharing with organizational communication as an intervening variable at PT. Indonesia Port IV (Persero) Makassar New Port Branch. This study uses saturated sampling technique, used a sample of 35 respondents’ employees of PT. Indonesia Port IV (Persero) Makassar New Port Branch. The research data were obtained from questionnaire (primary), literature study based on the purpose of the research. The analysis technique used the determination coefficient test (R2), multiple linear regression with hypothesis test, T test (partial) and Sobel Test. The results showed that work conflict has an indirect effect on knowledge sharing through organizational communication at PT. Indonesia Port IV (Persero) Makassar New Port Branch. Partially or directly, the work conflict variable on knowledge sharing has a significant influence. Then the work conflict on organizational communication has an insignificant influence. And organizational communication on knowledge sharing has a direct and significant effect.